FREQUENCY OF GENES POLYMORPHISM OF PRO-INFLAMMATORY CYTOKINES IN PATIENTS WITH CHRONIC ISCHEMIA OF CEREBRAL ISCHEMIA IN TRANSBAIKALIAN REGION - A. S. Knyazeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The results of research of occurrence of polymorphism of pro-inflammatory cytokines genotypes IL-1b (T-31C), IL-2(T330G), IL-6(C-174G), TNF(G-308A), IL-17A(G-197A), IL-17F (His-166Arg) in 195 patients with chronic cerebral ischemia are presented. The increase of frequency of a carriage of genotypes of IL-1β-31CC, IL-6-174GG, IL17A-197AA, IL17F-166ArgArg, alleles of IL-1β-31C, IL17F-166Arg is established (p < 0,05) in a clinical group.